Japan : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2020)
This Selected Issues paper assesses the relationship between demographic trends and housing prices in Japan. Among various issues in the context of regional disparities, the paper focus on regional differences in population dynamics to try and understand to what extent demographic trends have influenced housing market prices in Japan in the past twenty years. Large cities, notably the Greater Tokyo area, are experiencing net migration inflows, while other regions are experiencing net migration outflows. Due to the durability of housing compared to other forms of investment, the magnitude of house price declines associated with population losses is larger than that of house price increases associated with population gains. These model-based predictions are likely to underestimate the actual fall in house prices associated with future population losses, as expectations of lower housing prices in the future could trigger more population outflows and disposal of houses, especially in rural areas. The paper suggests policy measures to help close regional disparities and avoid potential over-investment by taking account of demographic trends for housing supply.